Evidence-based medicine, therapeutic efficacy and symbolic efficacy. “Dear ASL I WRITE YOU”: analysis of a corpus of letters sent to the Public Relations Office of ASLTO4 Piedmont - Luciano, Alessandra (E|C, 2020)
The article focused on the semiotic analysis of a corpus of complaint letters sent by patients to the Public Relations Office of a Hospital ASLTO4 Piemonte. The analysis of the letters provided information and data on the relationship between the perception of therapeutic efficacy and the positive relationship between doctor and patient. The semiotic analysis of the letters confirms recent outcomes of neurophysiology research, which show that the patient’s medical relationship influences the effects of placebo and nocebo and affects the perception of therapeutic and pharmacological efficacy.